Hubungan Bobot Lahir, Bobot Sapih dan Jenis Kelamin terhadap Paritas Sapi Simmental di BPTU HPT Padang Mengatas - Mega sari, rica; Harissatria, Harissatria; Afriani, Mila (Universitas Mahaputra Muhammad Yamin, 2020)
This study aims to determine the relationship between birth weight, weaning weight and sex on parity ofSimmental cattle in BPTU HPT Padang Mengatas. The material of this research is data from 104 Simmental parity I, IIand III cows kept in BPTU HPT Padang Mengatas. The method used in this research is a case study method and thesampling is done by purposive sampling. The data were obtained by looking at the Simmental cattle recording recordsin BPTU HPT Padang Mengatas. The variables observed were birth weight, weaning weight and sex as the independentvariable and parity as the dependent variable. Data analysis used multiple linear regression with stepwise method andits processing used SPSS 22 for windows to find variables that were significantly related to parity. The results of thisstudy indicate that the mean birth weight P1 = 34.94 kg; P2 = 43.11 kg; P3 = 45.93 kg. The average weaning weightP1 = 196.14 kg; P2 = 230.74 kg; P3 = 248.73 kg and the average gender P1 = 0.48; P2 = 0.52; P3 = 0.50. It can beconcluded that birth weight, weaning weight and sex of Simmental cattle have a significant relationship to parity ofSimmental cattle in BPTU HPT Padang Mengatas, because increased parity tends to increase birth weight and weaningweight of calves, calves with heavy birth weight tend to be male.